Can the new model of shared property rights promote better corporate financial performance in China? - Zihao Ma; Shuaishuai Zhang; Xiao Li; Jiahong Guo; Lidan Yang; Shixiong Cao (Financial Innovation)
Abstract Scientific research and technological innovation are driving modern economies; however, a new form of property rights is required to compensate knowledge workers for their contributions. In 1994, the Science and Technology Bureau of Shenzhen, China implemented a policy to encourage scientists and engineers to develop innovative technologies that would provide them a share of the profits earned from their innovations. This created a new “shared property rights” system. China’s shared property model is so new that the conditions under which it can improve enterprise profits remain unclear. To answer this question, we obtained data from the China Stock Market and Accounting Research database for 904 Chinese enterprises that had implemented shared property rights for the first time between 2009 and 2021 and used a propensity score matching method and econometric models to evaluate their performance. The results indicated that shared property incentives improved corporate financial performance and that benefits increased gradually over time. The new approach showed a stronger positive effect than restricted stock options during the study period. The strength of the incentive was greater for core technical staff than for senior executives, suggesting that scientists, engineers, and computer programmers should be the targets of a shared property rights incentive program. To take full advantage of the new shared property rights institution, enterprise managers should set the implementation period at a reasonable length (5 to 10 years, based on our study results). Enterprises can also test two or more simultaneous approaches that account for the specific needs of each category of workers, based on a careful examination of their current situation and expected or desired future situations.